SME bank selection and patronage behaviour in the Ghanaian banking industry - Narteh, B. (Emerald Group Publishing Limited, 2013)
Purpose – The paper aims to investigate small and medium-scale enterprises (SMEs) bank selection and patronage behaviour in the Ghanaian banking sector. Design/methodology/approach – A detailed literature review was used to identify five determinants of bank selection and other patronage factors which were used to survey 503 SMEs randomly selected from the data base of the National Board for Small Scale Industries in Ghana. Exploratory factor analysis, multiple regression and correlation analysis were used for the data analysis. Findings – The study found price competitiveness, credit availability, perceived service quality, staff attributes and bank attributes as determinants of SME bank selection. In addition, loans and overdrafts, cash collection, transfers, bank guarantees, advisory services and training were among the core services patronized by the SMEs. Practical implications – The study highlights the importance of factors considered important to the SME bank selection and patronage behaviour. It thus provides practical leverage to banks on how to attract, serve and retain SMEs in Ghana. Originality/value – The study is the first of its kind that investigated both bank selection and patronage behaviour at the same time and provides important insight for banks on how to attract, satisfy and manage SMEs. It also makes a major contribution to the literature on SME banking behaviour especially in a sub-Saharan Africa and responds to the recent call for more studies on SME practices in emerging economies.
Keywords: Ghana; SMEs; Bank selection; Patronage behaviour